Single stage treatment of diabetic calcaneal osteomyelitis with an absorbable gentamicin-loaded calcium sulphate/hydroxyapatite biocomposite: The Silo technique - Drampalos, E; Mohammad, H; Kosmidis, C; Balal, M; Wong, J; Pillai, A (Elsevier, 2017)
Background: Chronic osteomyelitis necessities appropriate infected bone and soft tissue excision. The authors describe the Silo surgical technique for the treatment of calcaneal osteomyelitis using a new antibiotic-loaded absorbable calcium sulphate/hydroxyapatite biocomposite. Methods: The Silo method involves debridement of the dead bone and local delivery of antibiotic in drilled tunnels using the biocomposite. It is combined with multiple sampling and culture-specific systemic antibiotic treatment guided by a multidisciplinary team. Twelve consecutive diabetic patients with heel ulcers and calcaneal osteomyelitis were treated with the above method. All had comorbidities (Cierny–Mader (C–M) Class B hosts). The mean age was 68 years (range 50–85). A retrospective review of radiographs and electronic medical records was conducted. Results: Patients were followed up until clinical cure of the ulcer for a mean of 16 weeks (range 12–18). Infection was eradicated in all 12 patients with a single stage procedure following a bone preserving technique. One patient required a subsequent flap operation and six vacuum-assisted closure (V.A.C.). There was also one case of prolonged wound leakage and no calcaneal fractures. Conclusions: The Silo technique is an effective method of local delivery of antibiotics and can be effectively implemented into the single-stage treatment of calcaneal osteomyelitis offering increased bone preservation and local delivery of antibiotic, decreasing the need for a major amputation.